2015
DOI: 10.1371/journal.pone.0123028
|View full text |Cite|
|
Sign up to set email alerts
|

Changes to Serum Sample Tube and Processing Methodology Does Not Cause Inter-Individual Variation in Automated Whole Serum N-Glycan Profiling in Health and Disease

Abstract: IntroductionSerum N-glycans have been identified as putative biomarkers for numerous diseases. The impact of different serum sample tubes and processing methods on N-glycan analysis has received relatively little attention. This study aimed to determine the effect of different sample tubes and processing methods on the whole serum N-glycan profile in both health and disease. A secondary objective was to describe a robot automated N-glycan release, labeling and cleanup process for use in a biomarker discovery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Both pre-operative as post-operative serum samples from cases had been stored at 20° C after centrifugation until monthly biobank collection and storage at 80° C, while serum samples from controls were stored directly at −80° C after centrifugation. Previously, it has been reported that glycans are not susceptible to changes in tubes used for sample storage or processing methodology [ 41 ]. Our long-term experience with glycan sample storage corroborates with these findings and has not pointed towards any type of glycan degradation during biobanking.…”
Section: Methodsmentioning
confidence: 99%
“…Both pre-operative as post-operative serum samples from cases had been stored at 20° C after centrifugation until monthly biobank collection and storage at 80° C, while serum samples from controls were stored directly at −80° C after centrifugation. Previously, it has been reported that glycans are not susceptible to changes in tubes used for sample storage or processing methodology [ 41 ]. Our long-term experience with glycan sample storage corroborates with these findings and has not pointed towards any type of glycan degradation during biobanking.…”
Section: Methodsmentioning
confidence: 99%
“…IgE samples were dried down before release. PNGase F release of N-glycans (E-PNG01; QA-Bio, http://glycotools.qa-bio.com) was performed in a manner similar to that previously published E4 . In short, 25-μg aliquots of the samples in water (17.5 μL) were incubated with 5 μL of 5× Reaction Buffer 7.5 and 1.25 μL of Denaturation Solution for 10 minutes at 100°C, followed by addition of Triton X-100 (1.25 μL) and PNGase F solution (1 μL) and incubation overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic release and fluorescent labelling of N-glycans from human blood plasma samples were performed using a highly automated analytical workflow for high-throughput (HTP) glycomics supported by a Hamilton STARlet liquid handling robot, as described previously [30,31] with minor modifications. Here, we used 4 µL of human blood plasma samples and a procainamide labelling kit with sodium cyanoborohydride as the reductant (LT-KPROC-96, Ludger) for fluorescent labelling of released N-glycans.…”
Section: N-glycan Release Fluorescent Labelling and Purificationmentioning
confidence: 99%